Identification of Cardiac CircRNAs in Mice With CVB3-Induced Myocarditis - Nie, Xiang; Fan, Jiahui; Li, Huihui; Wang, Jin; Xie, Rong; Chen, Chen; Wang, Dao Wen (Frontiers in Cell and Developmental Biology, 2022)
Background: Viral myocarditis could initial various immune response of the myocardium resulting in different severity of myocyte damage and subsequent cardiac dysfunction. The expression profiles and function of circRNAs in this process are unknown. Methods: Fulminant myocarditis (FM) and non-FM models were induced by coxsackie B3 virus (CVB3) in A/J mice and C57BL/6 mice, respectively. CircRNAs expression profiles were identified by RNA-seq. Quantitative RT-PCR, Spearman rank correlation, KEGG pathway and Western blot were performed for functional analysis of dysregulated circRNAs. Results: Severer inflammatory cells infiltration and cardiomyocyte necrosis were presented in CVB3-treated A/J mice rather than C57BL/6 mice. The dysregulated circRNAs in the 2 mouse strains both displayed strong correlation with the immune response, but A/J-specific dysregulated circRNAs were more prone to cardiac dysfunction. KEGG analysis indicated that the target genes of A/J-specific dysregulated circRNAs were mainly involved in viral infection, T cell and B cell receptor signaling pathway, while the target genes of C57BL/6-specific dysregulated circRNAs were absent in immune related pathways. Furthermore, knockdown of A/J-specific down-regulated circArhgap32 promoted cardiomyocytes apoptosis in vitro. Conclusion: Our data showed that cardiac circRNAs dysregulation is an important character of viral myocarditis.